A Study of Perfume Industry in District Kannauj and the Success of One District One Product Scheme (International Journal of Innovative Research in Engineering & Management, 2022)
The government of Uttar Pradesh  launched the One District One Product (ODOP) initiative  to promote domestic production of various handicrafts,  ready-to-wear garments, leather goods, etc. The state  government wants to promote local and specialised  products on a district-by-district basis. The UP  government is assisting local workers to increase their  income through product branding by assisting cottage and  small industries. The programmes have increased  employment opportunities for many artisans and  improved Uttar Pradesh's economy. This programme has  been put into effect by the Uttar Pradesh government in  each of the state's 75 districts. The programme has  received success and praise both domestically and  internationally. Present study is an effort to study the  perfume industry of District Kannauj in the light of  ODOP scheme in Uttar Pradesh.
Keywords: ODOP scheme; Perfume Industry; Administration; Management